Posisi Daya Saing Produk dan Kelembagaan Agroindustri Halal ASEAN - Dwi Purnomo; Endang Gumbira Said; Anas M Fauzi; Khaswar Syamsu; Muhammad Tasrif (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2011)
-